A comparison of performance and exhaust emissions with different valve lift profiles between gasoline and LPG fuels in a SI engine. (25th August 2016) - Çinar, Can; Şahin, Fatih; Can, Özer; Uyumaz, Ahmet
Highlights: Volumetric efficiency improved with the increase of valve lift in case of LPG usage. Lower CO and HC emissions were obtained with LPG compared to gasoline. NOx emissions increased with LPG according to gasoline for both valve lifts due to higher cylinder gas temperature. Engine performance values with LPG get closer to the gasoline when higher valve lift is used. Abstract: In this study, a single-cylinder, four-stroke, single overhead camshaft (SOHC), spark ignition (SI) gasoline engine was converted to run with liquefied petroleum gas (LPG) fuel. To improve the volumetric efficiency, the camshaft of the engine was re-designed using classical spline method for different valve lifts. The variations of engine brake torque, power, brake specific fuel consumption (BSFC), HC, CO, CO2 and NOx emissions and exhaust gas temperature were investigated with unleaded gasoline and LPG fuels for different valve lifts. The experiments were conducted at 1700–3200 rpm engine speeds range at wide open throttle (WOT) and λ = 1. Engine torque and power decreased and BSFC increased with LPG fuel for the 7 mm valve lift. Brake engine torque decreased by 8.82% and BSFC increased by 7.25% with LPG fuel compared to gasoline for 7 mm valve lift at 2600 rpm engine speed. However, HC and CO emissions decreased, NOx emissions increased with the usage of LPG fuel. HC and CO emissions decreased by 18.24% and 5.3%, respectively, and NOx emissions increased by 7.67%, with LPG fuel at 2600 rpm engine speed. An improvement was observed on engine torque, BSFC, HC and CO emissions with the increase of the valve lift to 8 mm and LPG fuel. At the low engine speeds, engine performance and exhaust emissions deteriorated with the increase of valve lift for gasoline fuel, while improvements were found at middle and higher engine speeds.